177k views
1 vote
Solve the following equation

please it's urgent




3a + 5b = -9 , 2a + 5b = -11​

User Igor Benko
by
4.5k points

1 Answer

4 votes

Answer:

a = 2

b = -3

Explanation:

Here, we want to solve the two equations simultaneously

since we have the same 5b term in both, we can subtract the second equation from the first

we have this as;

3a-2a = -9 -(-11)

a = -9+ 11 = 2

Recall;

2a + 5b = -11

2(2) + 5b = -11

5b = -11-4

5b = -15

b = -15/5

b = -3

User FloChanz
by
4.9k points